INFLUENCE OF RUSSIAN AND EUROPEAN LITERATURE ON UZBEK CHILDREN’S STORYTELLING - Fozilova Odina Nabiyevna (Zeta Repository, 2023)
The article discusses changes in Uzbek children’s literature in different eras. Based on the analysis of specific works for children and youth, the author shows the influence of Russian literature on Uzbek literature.